Utility of Pelvic MRI and Tumor Markers HE4 and CA125 to Predict Depth of Myometrial Invasion and Cervical Involvement in Endometrial Cancer - Narges Zamani; Mitra Modares Gilani; Fateme Zamani; Hossein Zamani (Journal of Family and Reproductive Health, 2016)
Objective: The purpose of this pilot study was to determine whether the MRI and biomarkers human epididymis protein 4 (HE4) and CA125 correlate with depth of myometrial invasion, histologic grade, cervical involvement and nodal metastases in patients with endometrioid adenocarcinoma of the uterus. Materials and methods: This was a prospective, observational study in women with biopsy-proven endometrial adenocarcinoma of the uterus. Preoperative pelvic MRI was performed and concentration of HE4 and CA125 were assessed before surgery. All surgical specimens were reviewed by a single expert pathologist. The results were compared with the final histopathology report of surgical staging. Results: Included were a total of 68 women with endometrioid adenocarcinoma of the uterus, most (76%) with stage I disease. Levels of serum HE4 greater than 140PM and CA125 greater than 35 ku/L were observed in 12 (17%) and 26 (38.2%) of patients respectively whose greater proportion were cases with deep myometrial invasion and high grade tumor. In the evaluation of deep tumoral invasion (> 50%) of the myometrium sensitivity, specificity, and diagnostic accuracy of MRI were 68.9%, 94.8% and 83.8% respectively. For lymph node involvement these values were 50%, 95.1% and 91.1% respectively and for cervical stromal involvement were 64.3%, 98.1% and 91.1% respectively. Conclusion: Higher stage, deep myometrial invasion, and lymph node or cervical stromal involvement increase diagnostic accuracy of MRI. Higher levels of HE4 and CA125 were observed in patients with deep myometrial invasion and higher grade of tumor.